Стратегічні аспекти розвитку інноваційно-інтегрованих структур в Україні : основні складові та сучасний інструментарій - Левченко, О. М.; Ткачук, О. В.; Levchenko, О.; Tkachuk, О. (ЦНТУ, 2017)
Стаття присвячена вивченню стратегічних аспектів розвитку інноваційно-інтегрованих структур в Україні в умовах глобалізації економічних відносин у світі. На підставі аналізу процесів у сфері інноваційної діяльності та соціально-економічного розвитку країни в цілому констатовано відсутність сприятливих передумов для значного поширення інноваційно-інтегрованих структур на сучасному етапі розвитку вітчизняної економіки та підкреслено доцільність стратегічного підходу до регулювання процесів їх створення та розвитку в Україні. Визначено мету та зміст основних складових стратегічного підходу до розвитку інноваційно-інтегрованих структур, таких як стратегічний аналіз та моніторинг, стратегічне прогнозування, стратегічне планування, стратегічне управління. Обґрунтовано особливості застосування сучасного стратегічного інструментарію розвитку інноваційно-інтегрованих структур, до якого віднесені форсайт-дослідження, брендинг територій, територіальний бенчмаркінг, програмно- цільовий метод, метод сценаріїв тощо. The paper is devoted to the research of strategic aspects of the development of innovative-integrated structures in Ukraine in the conditions of the globalization of economic relations in the world. The relevance of developing the innovative strategies of economy's management at the level of state and its regions, implementation the effective innovation policy and appropriate mechanisms for its realization with using the modern forms, methods, levers, instruments of regulation of the innovation processes are emphasized. On the basis of the analysis of tendencies in the sphere of innovation activity and socio-economic development of the country as a whole, the lack of favorable prerequisites for the significant dissemination of innovative-integrated structures at the current stage of development of the national economy has been stated. The expediency of a strategic approach to the regulation of the processes of creation and development of the innovative-integrated structures in Ukraine has been underlined, which is aimed to the long-term management on basis the defined goals and using the set of means regarding their achievement, taking into account the actions of external and internal conditions and the dynamics of their change. The purpose and content of the main components of the strategic approach to the development of innovative-integrated structures, such as a strategic analysis and monitoring, strategic forecasting, strategic planning, strategic management, are defined. The peculiarities of applying of the modern strategic instrumentation of development of the innovativeintegrated structures are substantiated to which of what are been: a foresight research, branding of territories, territorial benchmarking, program-target method, scenario method, etc.
The strategic aspects of the development of innovative integrated structures in Ukraine : basic components and contemporary instrumentation
Keywords: стратегія; стратегічний інструментарій; інноваційна модель економіки; інноваційно-інтегрована структура; форсайт; бенчмаркінг; брендинг; strategy; strategic instrumentation; innovative model of economy; innovative-integrated structure; foresight; benchmarking; branding